(untitled) (Heritage, 2022)
Vojislav (Vuk) Bakic was born in Kordun, in the village of Perna in 1847. At that time his place of birth was in the space never precisely defined by a consistent border between Kordun and Banija as a part of Vojna Krajina which was then and a few decades later still under the direct jurisdiction of Vienna. That is how he had an early opportunity to learn German language. That fact together with his natural talents and other opportunities gave him a chance to improve his studies in Leipzig and Heidelberg. He received his PhD in Leipzig. Apart from professional literature in German, Bakic regularly used literature in French, English and Italian language. He also spoke Latin and Czech. He followed closely development of education in Serbia, surrounding countries and Europe in general. His pedagogical work took place in times when pedagogy and psychology were separating from philosophy. In that time, system of education was established as a part of modern social system. That is why the work of Vojislav Bakic must be regarded in the context of history of pedagogical science in Serbia, and at a lower level as an impact on the development of pedagogy as a science in Serbia in those times. He is an extraordinarily prolific writer of valuable pedagogical works. He was considered a pioneer in a number of pedagogical disciplines within the pedagogical science. He advocated for the high education of secondary school teachers in Serbia. He turned pedagogy into a university discipline.He organized studies of pedagogy in Serbia at the European level at the time.